EULAR recommendations for intra-articular therapies. Issue 10 (25th May 2021) - Uson, Jacqueline; Rodriguez-García, Sebastián Cruz; Castellanos-Moreira, Raul; O'Neill, Terence W; Doherty, Michael; Boesen, Mikael; Pandit, Hemant; Möller Parera, Ingrid; Vardanyan, Valentina; Terslev, Lene; Kampen, Willm Uwe; D'Agostino, Maria-Antonietta; et al.
Abstract : Objectives: To establish evidence-based recommendations to guide health professionals using intra-articular therapies (IAT) in adult patients with peripheral arthropathies. Methods: A multidisciplinary international task force established the objectives, users and scope and the need for background information, including systematic literature reviews) and two surveys addressed to healthcare providers and patients throughout Europe. The evidence was discussed in a face-to-face meeting, recommendations were formulated and subsequently voted for anonymously in a three-round Delphi process to obtain the final agreement. The level of evidence was assigned to each recommendation with the Oxford levels of evidence. Results: Recommendations focus on practical aspects to guide health professionals before, during and after IAT in adult patients with peripheral arthropathies. Five overarching principles and 11 recommendations were established, addressing issues related to patient information, procedure and setting, accuracy, routine and special aseptic care, safety issues and precautions to be addressed in special populations, efficacy and safety of repeated joint injections, use of local anaesthetics and aftercare. Conclusion: We have developed the first evidence and expert opinion-based recommendations to guide health professionals using IAT. We hope that these recommendations will be included in different educational programmes, used by patient associations and put into practice via scientific societies to help improve uniformity and quality of care when performing IAT in peripheral adult joints.